Immersion and Emotional Arousal with Virtual Reality Videogames - Torres Fernández, David (2021)
This research studies the association between immersion in Virtual Reality (VR) videogames and emotional activation. Responses to a videogame in a VR setting and in a no VR setting were compared. The study uses a within-subject design with 97 university students. Heart rate and self-perceived emotional state were measured. Results show higher immersion levels and heart rate in the VR condition. Perceived emotional state predicted immersion in both conditions, nevertheless, in the no VR condition higher scores in both, positive and negative, emotions were related with higher immersion experience, while in the VR condition only positive emotions were related with higher immersion. The implications and relevance of these findings are discussed.